2022
DOI: 10.1186/s12951-022-01394-w
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase IX-targeted H-APBC nanosystem combined with phototherapy facilitates the efficacy of PI3K/mTOR inhibitor and resists HIF-1α-dependent tumor hypoxia adaptation

Abstract: Background Non-redundant properties such as hypoxia and acidosis promote tumor metabolic adaptation and limit anti-cancer therapies. The key to the adaptation of tumor cells to hypoxia is the transcriptional and stable expression of hypoxia-inducible factor-1 alpha (HIF-1α). The phosphorylation-activated tumorigenic signal PI3K/AKT/mTOR advances the production of downstream HIF-1α to adapt to tumor hypoxia. Studies have elucidated that acid favors inhibition of mTOR signal. Nonetheless, carboni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…(g) Immunofluorescence images of expressed HIF-1αin different groups. Reprinted with permission under a Creative Commons CC BY License from ref . Copyright (2022) BioMed Central.…”
Section: Hypoxia-relieving Strategies Based On Nanomedicinementioning
confidence: 99%
See 1 more Smart Citation
“…(g) Immunofluorescence images of expressed HIF-1αin different groups. Reprinted with permission under a Creative Commons CC BY License from ref . Copyright (2022) BioMed Central.…”
Section: Hypoxia-relieving Strategies Based On Nanomedicinementioning
confidence: 99%
“…298 Besides, Liu et al constructed a drug delivery nanoplatform by encapsulating BEZ235 and photosensitizer Ce6 in 4-(2aminoethyl) benzenesulfonamide and PEG-NH 2 modified hollow polydopamine to reduce tumor acidification, block the PI3K/mTOR signal, and slow down HIF-1α-dependent tumor adaptation to low O 2 for phototherapy (Figure 8f). 294 In detail, carbonic anhydrase IX inhibitor, 4-(2-aminoethyl) benzenesulfonamide, which can cause intracellular acidification, has shown excellent antitumor effects in some research. The BEZ235 can be released in an acid microenvironment to inhibit the PI3K/AKT/mTOR pathway and suppress HIF-1α expression, thus resisting HIF-1α-dependent tumor hypoxia adaptation (Figure 8g).…”
Section: Hypoxia-relieving Strategies Based On Nanomedicinementioning
confidence: 99%
“…A polyvinyl caprolactam–polyvinyl acetate–polyethylene glycol (PVCL–PVA–PEG) graft copolymer (Soluplus) encapsulated BA micelle (Soluplus-BA) was fabricated and results showed that Soluplus-BA micelles increased the inhibitory effect of BA on the angiogenesis by regulating the HIF-1/VEGF-FAK signaling pathway in breast cancer MDA-MB-231 cells ( Qi et al, 2021 ). Recently a photodynamic therapy based on conjugated PNPs for BC has been reported ( Liu et al, 2022 ). Ying Zhang et al (2022) synthesized photochemical-responsive nanoparticle by incorporating DOX, curcumin (CUR), and perfluorooctyl bromide (PFOB) into poly (lactic-co-glycolic acid) (PLGA) via double emulsification (DOX-CUR-PFOB-PLGA).…”
Section: Therapeutic Strategies Targeting Hif-1α In Bcmentioning
confidence: 99%
“…A drug delivery nanoplatform equipped with dual PI3K/mTOR inhibitor Dactolisib (NVP-BEZ235, BEZ235) and CAIX inhibitor 4-(2-aminoethyl) benzene sulfonamide (ABS) was designed to form HPDA-ABS/PEG-BEZ235/Ce6 (H-APBC) nanoparticles. The study showed that the H-APBC could produce ROS upon light irradiation and release of BEZ235 from H-APBC in acid microenvironment could mitigate PI3K/mTOR signal and resist HIF-1α-dependent tumor hypoxia adaptation ( Liu et al, 2022 ). Photodynamic therapy (PDT) has become an emerging area of modern medicine.…”
Section: Therapeutic Strategies Targeting Hif-1α In Bcmentioning
confidence: 99%
“…Carbonic anhydrase IX (CAIX) is a transmembrane protein that is triggered by the high expression of hypoxia-inducing factor 1 (HIF-1) in most tumor tissues at hypoxic sites. Its main function is to catalyze the hydration of CO 2 to generate hydrogen protons and bicarbonate, thereby regulating the pH homeostasis within and without the cell. Once CAIX overexpression leads to a slightly TME change, it can combine with hypoxic conditions to promote tumor growth and angiogenesis, facilitate tumor metastasis, and interfere with the expression of genes and related proteins. , …”
Section: Introductionmentioning
confidence: 99%